Recensiones - Fernández, Inés; Cardenal, Rodolfo; García, Juan José; Carranza, Salvador (ECA: Estudios Centroamericanos, 1990)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 45, No. 505-506, 1990: 1059-1069.